Project-based Learning in Teaching Subtitling Course at English Study Program Politeknik Negeri Jember - Titik Ismailia (Politeknik Negeri Jember, 2022)
This paper aimed to describe the implementation of project-based learning in teaching subtitling course of English Study Program Politeknik Negeri Jember. Project-based learning is an approach in classroom that is designed to engage students to do deep investigation on complex and authentic problem then making products. It is a kind of method that uses problems as a first step in collecting and integrating new knowledge based on experience in real activity. The steps are; (1) driving questions; (2) focus on learning goals; (3) scientific practices; (4) collaborative activities; (5) learning technology scaffold; (6) creation of artifact. After finishing the whole activities, all students were able to produce a video subtitling in 5 to 7 minutes long. It also helped them to work effectively and do collaborative work with their peers.